Performance of In-Line Microfluidic Mixers in Laminar Flow for High-Throughput Flow Cytometry - W. Coyt Jackson; T.A. Bennett; B.S. Edwards; E. Prossnitz; G.P. Lopez; L.A. Sklar (BioTechniques, 2002)
We describe a micromixing approach that is compatible with commercial autosamplers, flow cytometry, and other detection schemes that require the mixing of components that have been introduced into laminar flow. The scheme is based on high-throughput flow cytometry (HyperCyt™) where samples from multi-well plates that have been picked up by an autosampler can be separated during delivery by the small air bubbles introduced during the transit of the autosampler probe from well to well. Here, either cell or particle samples flowing continuously and driven by a syringe are brought together in a Y with reagent samples from wells driven by a peristaltic pump. The mixing is driven by a magnetic microstirrer contained within the sample line. The mixing is assessed using fluorescence of both cell calcium responses and bead-based fluorescence unquenching. In the analysis stream, the particles and reagents are mixed with either a “wire” or “bar”. The bar is more efficient than the wire, and the efficiency of either depends on the spinning action. The high-throughput approach and mixing in HyperCyt integrate autosamplers with submicroliter detection volumes for analysis in flow cytometry or in microfluidic channels.